Social-contextual determinants of parental behaviour of preschool children’s mothers and fathers - Štironja Borić, Ana (Array, 2011)
Based on Belsky's (1984) model of parenting determinants, the study examined the contribution of social-contextual factors (quality of marriage indexed by marital satisfaction, perceived social support and parent-employee interrole conflict) to individual differences in parenting behaviour of parents of preschool children. The sample of participants was made up of 130 married and employed couples with preschool children. They were asked to fill in the questionnaires on demographic factors, dimensions of parenting behavior (positive parenting, negative parenting and permissiveness), and features of social context. The results showed that by features of social context only positive parenting could be predicted, but not negative parenting and permissiveness. Marital satisfaction and social support were significant contextual predictors for positive maternal parenting. Social support was a significant predictor for positive paternal parenting. The results did not support Belsky's hypothesis of marital relationship as the key contextual determinant of parenting.